Analysis of The Influence of Environmental Factors, Wage Factors, Coordination And Worker Productivity That Influence The Performance of Government Project Completion Time in Pangkalpinang City - Fanta Wahyu Giarta; Agus Suroso (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of environmental factors, wage systems, coordination, and worker productivity on the completion time performance of government building construction projects in Pangkalpinang City. Using descriptive quantitative methods and multiple linear regression analysis, the results of the study indicate that these four variables simultaneously contribute 85.4% to project completion. The wage factor is the dominant factor with a contribution of 72.59%, indicating that an effective wage system can improve the efficiency of project completion. Possible solutions include providing wages based on skills, work duration, performance, type of work, and incentives to increase worker productivity. This study provides recommendations for project managers to optimize workforce management strategies to ensure projects are completed on time with optimal quality.